1998
DOI: 10.1063/1.477206
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of N(2 2D) with methane and deuterated methanes

Abstract: NH radicals and H atoms were identified as products in the reaction of N(2D) with CH4. The absolute yields of NH and H were determined to be 0.3±0.1 and 0.8±0.2, respectively. The rotational state distributions of NH (v″=0) for CH4 and partially deuterated methanes, CHnD4−n (n=1–3), are single modal and peak at N″=13±2, while the vibrational population ratios, NH (v″=1)/NH (v″=0), are 0.6. The rotational energy distribution of ND (v″=0) from CD4 is similar to that for NH (v″=0). The ND (v″=1)/ND (v″=0) ratio i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
76
3

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(81 citation statements)
references
References 20 publications
2
76
3
Order By: Relevance
“…It should be noted that ab-initio calculations with DFT and CCSD methods lead to the absence of a barrier for the insertion (Balucani et al 2009). The N( 2 D) + CH 4 reaction has been studied experimentally in detail by Umemoto et al (1998) found a ratio between H 2 CNH + H/NH + CH 3 equal to 0.8/0.3. Balucani et al (2009) studied this reaction in a crossed beam experiment at high collision energy (above 22 kJ mol −1 which corresponds to T > 2600 K) suggesting an increasing NH branching ratio with the temperature and also H 2 CNH and CH 3 N production.…”
Section: A2 Hcn → Hnc Isomerizationmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be noted that ab-initio calculations with DFT and CCSD methods lead to the absence of a barrier for the insertion (Balucani et al 2009). The N( 2 D) + CH 4 reaction has been studied experimentally in detail by Umemoto et al (1998) found a ratio between H 2 CNH + H/NH + CH 3 equal to 0.8/0.3. Balucani et al (2009) studied this reaction in a crossed beam experiment at high collision energy (above 22 kJ mol −1 which corresponds to T > 2600 K) suggesting an increasing NH branching ratio with the temperature and also H 2 CNH and CH 3 N production.…”
Section: A2 Hcn → Hnc Isomerizationmentioning
confidence: 99%
“…Moreover, as HNC is produced mainly with high internal energy there is a possibility of rate enhancement. For relaxed HNC we recommend the rate constant calculated by Sumathi & Nguyen (1998) The N( 2 D) + CH 4 reaction has been studied experimentally Umemoto et al 1998) and theoretically (Ouk et al 2011;) and a review has been performed by Herron (1999). Theoretical calculations suggest two pathways for this reaction, direct H atom abstraction and N( 2 D) insertion in one C-H bond, both mechanism presenting a barrier in the entrance valley (Ouk et al 2011;.…”
Section: A2 Hcn → Hnc Isomerizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we added 19 reversible reactions to the C/H/O/N mechanism, which describe the kinetics of O( 1 D) and N( 2 D), including radiative and collisional desexcitation. These reactions rates are taken (or have been estimated) from Okabe (1978), Herron (1999), Umemoto et al (1998), Balucani et al (2000a), Sato et al (1999), Balucani et al (2000b), and Sander et al (2011).…”
Section: Excitation Of Oxygen and Nitrogen Atomsmentioning
confidence: 99%
“…A much stronger effect of this kind was observed for the N + CH 4 system [28], when the luminescence from N( 4 S) + CH 4 and N( 2 D) + CH 4 was compared. Although the N + CH 4 system is not isoelectronic with the one studied here, it is nevertheless believed to behave analogously when it comes to reaction dynamics of the metastable D-state [32]. For the N + CH 4 system, very efficient formation of CH(A,B) at energies below 40 eV CM was found to be a signature of the reaction of fast metastable N( 2 D) atoms, the reaction proceeding via insertion of an N atom into the C-H bond, with subsequent dissociation of the complex, a dissociation in which CH(A)-formation is the most exothermic luminescent channel.…”
Section: Resultsmentioning
confidence: 99%